Viral hepatitis - Thomas, H. C. (Howard C.) (Wiley Blackwell, 2014)
Written and edited by world's leading authorities, the new edition of this leading textbook features new chapters covering the very latest developments in extrahepatic manifestations and new anti-viral treatments for HBV and HCV. With individual sections on each strain of hepatitis, the text offers a level of detail unmatched by any other reference.